1977
DOI: 10.1159/000241013
|View full text |Cite
|
Sign up to set email alerts
|

Skin Barrier Properties in the Newborn

Abstract: Relative permeabilities of newborn and adult skin to small molecules were determined by measuring emission of carbon dioxide and water vapor through skin. Transepidermal water loss (TEWL) measured on the forearm of 22 term infants was lower than that observed in 30 control adults (0.31 ± 0.09 vs. 0.39 ± 0.15 mg/cm2/h). There was no significant difference between newborn carbon dioxide emission rates (CDER) and adult CDER. When environmental temperature was raised from 74 to 80 °F, large dramatic inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Term babies (group 1) had low rates of evaporation over most of the body but water losses from the palms and the soles were high. Cunico et al (1977) suggested that the higher values at these sites in a comfortable thermal environment were due to mild sweating. In both adults and babies, skin water loss and basal metabolic rate are directly related (Levine and Marples, 1930;Hey _ and Katz, 1969), so the higher water loss in adults might simply be due to the fact that they have higher *.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Term babies (group 1) had low rates of evaporation over most of the body but water losses from the palms and the soles were high. Cunico et al (1977) suggested that the higher values at these sites in a comfortable thermal environment were due to mild sweating. In both adults and babies, skin water loss and basal metabolic rate are directly related (Levine and Marples, 1930;Hey _ and Katz, 1969), so the higher water loss in adults might simply be due to the fact that they have higher *.…”
Section: Resultsmentioning
confidence: 96%
“…Total insensible water loss from the skin and respiratory tract has been measured using a metabolic chamber Zweymuller and Preining, 1970), or by measurement of weight loss Fanaroff et al, 1972;Wu and Hodgman, 1974;Marks et al, 1977). Measurements of skin water loss from isolated sites have been made using a ventilated capsule (Foster et al, 1969;Cunico et al, 1977). Results suggest that skin water loss is low in term babies, but that in preterm ones, whether nursed naked in standard incubators or under radiant warmers or phototherapy, losses are high.…”
mentioning
confidence: 99%
“…Full term newborn infant skin has a thick epidermis, well-formed stratum corneum (SC), and low transepidermal water loss, indicating a highly effective barrier (1). It undergoes maturational changes for months after birth, including a rapid decrease then increase in SC hydration, decreasing surface acidity with acid mantle development and appearance of functional toll-like receptors (TRP3, during gestation and postnatally) for innate immunity (25).…”
Section: Introductionmentioning
confidence: 99%
“…Using TEWL as the gold standard, the literature evidence shows that full-term neonates have completely developed permeability barrier function at birth. High TEWL was shown in the first 4 h after birth, while TEWL afterwards returned to values of lower than 10 g/m 2 /h (normal range for healthy skin under basal conditions), suggesting ongoing drying of the skin immediately after birth [3,4,9,20]. However, depending on the exposure conditions (open to air, semiocclusive, occlusive) and the physicochemical properties of the permeants and the composition of the vehicle, dermal penetration and systemic bioavailability may be increased for compromised skin conditions such as premature infant skin, or in diaper dermatitis areas.…”
Section: Discussionmentioning
confidence: 99%
“…TEWL measures the steady-state water flux that passes through the epidermal layer to the surrounding atmosphere via diffusion and evaporation [9,10]. TEWL has been used as an indicator of skin integrity deficiencies, like damage from chemical or physical irritants or changes under occlusive conditions [11,12,13,14].…”
Section: Methodsmentioning
confidence: 99%